Review of the Latest Theories of Education: Pedagogy 2.0, Education 3.0 and Heutagogy (Journal of Educational Sciences, 2020)
The Internet system has created new qualitative opportunities for the development of education. The creation of a global information infrastructure in the 90s of the XX century transormed the world, making it dynamic, rich in information and compressed. A new generation of pupils and students born in the era of the Internet has grown. Gradually, pedagogy is changing, in other words, expanding its foundations for new teaching strategies for schoolchildren and students, as well as adults. In this article, we will discuss elements of emerging theories – “Pedagogy 2.0” and “Pedagogy 3.0”, “Education 2.0”, “Education 3.0”, Heutagogy, digital pedagogy and their continuity. Are these theories revolutionary in modern education? How do Pedagogy 3.0 and Education 3.0 intersect with digital technology, and in a new way, with digital pedagogy? Is it necessary for teachers to maintain / reorganize the system of training pedagogues and how? The article is of an overview nature. A version for ordering views on modern pedagogy is proposed for discussion. As it is known, in the discussion new ideas and new learning strategies for students can be born. The generalization of experience is used in the course on “Methods of teaching pedagogy”, “Designing in education.” A directed interview with students of pedagogical specialties was carried out and their assessment of the advantages and disadvantages of “pedagogy – androgogy – eutagogy” in modern pedagogical practice is given.